THE EFFECT OF BRAND IMAGE AND PRODUCT QUALITY ON PURCHASE DECISIONS IN J.CO DONUTS IN MALANG CITY - Delviera, Sahara; Evelina, Tri Yulistyawati (Jurnal Aplikasi Bisnis, 2024)
The research location is in Malang City with a sample of all J.CO Donut's consumers in Malang City. Minimum age of 17 years old, totalling 100 respondents. This study used a questionnaire data collection technique and used a purposive sampling technique. Data processing using SPSS for Windows. The coefficient of determination test, it was found that the contribution of brand image and product quality to the purchasing decision of J.CO Donut's in Malang City was 4.9 percent. (1) Brand image partially has a positive but not significant effect on purchasing decisions; (2) product quality partially has no positive but significant effect on purchasing decisions; (3) Brand image and product quality simultaneously have a positive and significant effect on purchasing decisions for J.CO Donuts in Malang City. The author suggests for future researchers, it is hoped that the results of this study can be a reference and input to add insight. For the company, it is expected to be able to maintain the brand image of J.CO Donuts products. For the State Polytechnic of Malang, it is hoped that this research can be used as a reference for further research.